Study on performance enhancement of anaerobic digestion of municipal sewage sludge - Yeneneh, Anteneh Mesfin (Curtin University, 2014)
This research focuses on investigating effects of combined microwave-ultrasonic pretreatment of municipal sewage sludge on anaerobic digester performance. Application of a novel combined microwave-ultrasonic pretreatment on thickened excess activated and mixed sludge significantly improved methane production, volatile solid and COD reduction, digestion kinetics, pathogen removal and dewaterability. Effects of Organic loading rate, sludge retention time and sludge mixing ratio were studied. Microwave and ultrasonic pretreatment conditions and digester operational parameters were optimized using experimental and modelling techniques.